2019
DOI: 10.12659/msm.914654
|View full text |Cite
|
Sign up to set email alerts
|

Mean Corpuscular Volume Predicts In-Stent Restenosis Risk for Stable Coronary Artery Disease Patients Receiving Elective Percutaneous Coronary Intervention

Abstract: Background The purpose of this study was to analyze predictive performance of MCV in midterm ischemic events among SCAD patients undergoing elective PCI. Material/Methods We retrospectively included 226 consecutive patients with SCAD who received elective PCI. The patients were grouped based on MCV quartile values. The prognostic significance of MCV was assessed using univariate and multivariate Cox proportional hazard regression analyses. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 25 publications
0
13
1
Order By: Relevance
“…16 Conversely and similar to our results, Sun et al described an association of MCV with restenosis and MI after PCI for stable CAD, with the lowest quartile of MCV representing the highest risk. 17 The discrepancy between our results and the former studies might be based on several factors: our cohort and the cohort included by Sun et al consisted exclusively of patients with stable atherosclerotic disease, while both other studies demonstrating an association of high MCV with atherothrombotic outcomes at least in part included ACS patients. Moreover, only 1 patient in our cohort fulfilled the common criteria of macrocytosis (MCV >100 fL), therefore hindering comparability.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…16 Conversely and similar to our results, Sun et al described an association of MCV with restenosis and MI after PCI for stable CAD, with the lowest quartile of MCV representing the highest risk. 17 The discrepancy between our results and the former studies might be based on several factors: our cohort and the cohort included by Sun et al consisted exclusively of patients with stable atherosclerotic disease, while both other studies demonstrating an association of high MCV with atherothrombotic outcomes at least in part included ACS patients. Moreover, only 1 patient in our cohort fulfilled the common criteria of macrocytosis (MCV >100 fL), therefore hindering comparability.…”
Section: Discussioncontrasting
confidence: 84%
“…16 In contrast, low MCV has been associated with the rate of restenosis and MI in patients undergoing PCI for stable CAD. 17 However, to the best of our knowledge, no study addressing the association of MCV with adverse outcomes in peripheral artery disease (PAD) has been published, so far. The objective of the present study was to investigate the prognostic value of MCV for long-term adverse cardiovascular outcomes in a cohort of patients with PAD undergoing successful infrainguinal angioplasty with stent implantation.…”
Section: Introductionmentioning
confidence: 99%
“…Iron deficiency is also associated with diminished mitochondrial function 24,25 , and endothelial 8 and skeletal muscle 26 dysfunction, which in turn results in increased rates of heart failure 24 , cardiovascular disease 25 , and sarcopenia due to skeletal muscle myopathy 26 . Moreover, several clinical studies in patients with stroke and CVD have demonstrated similar associations of microcytic anemia with such clinical outcomes as unfavorable functional outcomes; hospitalization and inpatient mortality 27,28 ; and restenosis after percutaneous coronary intervention 29 . The absence of an association between MCV and CVD outcomes in our present study is likely explained by the lower incidence of CVD events among Japanese patients on hemodialysis than in other countries.…”
Section: Discussionmentioning
confidence: 96%
“…However, the conflicting evidence regarding MCV level and cardiovascular outcomes is reported. Stable CAD patients undergoing PCI in the 1st quartile who had the lowest MCV values exhibited a high risk of restenosis [22]. Obviously, the target population of this study are participants with stable CAD, and their aim is to explore the association between MCV and incident restenosis; these details are very different from those of our study.…”
mentioning
confidence: 83%
“…It is reduced in diabetes, probably because iron deficiency anemia is common in people with diabetes [17,18]. Studies demonstrate that MCV is associated with the prognosis of several diseases, including peripheral arterial disease, CAD, and cerebral ischemic stroke [19][20][21][22][23]. The possible mechanism is that the increase of MCV impairs the antioxidant capacity of erythrocytes and decreases endothelial function, both of which promote the development of atherosclerosis [24].…”
Section: Introductionmentioning
confidence: 99%